New Technique of Embolization of the Hemorrhoidal Arteries Using Embolization Particles Alone: Retrospective Results in 33 Patients - Karim Abd El Tawab; Amr Abdo Salem; Rana Khafagy (The Arab Journal of Interventional Radiology)
Purpose: The purpose of this study was to assess the safety and efficacy of using particles only in the embolization of the hemorrhoidal arteries for the management of hemorrhoids. Subjects and Methods: This is a retrospective study for patients treated between March 2015 and December 2018. We treated 33 patients, 13 men and 20 women with a mean age of 37 years (range: 18–70 years), in which 11 patients had Grade II hemorrhoids and 22 had Grade III hemorrhoids. Technical and clinical successes together with procedural complications were assessed. Results: The technical success rate was 100%. No minor or major complications have been reported. No cases of anorectal ischemia, anal incontinence, hemorrhoidal thrombosis, or complications related to femoral arterial puncture have occurred. Follow-up was at 3 months and 12 months postembolization. Clinical success was observed in 32 patients (96.9%) with improvement by at least 2 points of the French bleeding score at 3 months postembolization. Conclusion: The use of particles alone in the embolization of hemorrhoidal arteries whether from the superior rectal artery and/or from the middle and inferior rectal arteries can offer a safe and effective treatment option.